(untitled) (International Journal of Environmental Sciences, 2025)
The planning and control software for a teleoperating robot system used in minimally invasive surgery is the main topic of this study. It incorporates capabilities like force feedback control, null-space handling for three robot arms, and robot setup planning to address the challenge of controlling a system with 41 degrees of freedom. Sequential planning and registration procedures make up the planning software. To account for operating room variances, a virtual reality version of the optimum setup is scaled up. The hierarchical levels of the real-time control system guarantee accurate and effective robotic system control. Because of its modular design, the system can be expanded and modified without sacrificing functionality. During teleoperation, it improves the surgeon’s accuracy and control with both hands by giving them intuitive force feedback and hand-eye coordination.